Recent Advances in C-S-H Nucleation Seeding for Improving Cement Performances - Cuesta-García, Ana María; Morales-Cantero, Alejandro; Gómez-de-la-Torre, María de los Ángeles; García-Aranda, Miguel Ángel (MDPI, 2023)
Reducing cement CO2 footprint is a societal need. This is being achieved mainly by replacing an increasing amount of Portland clinker by supplementary cementitious materials. However, this comes at a price: lower mechanical strengths at early ages due to slow pozzolanic reaction(s). This is being addressed by using accelerator admixtures. In this context, calcium silicate hydrate nucleation seeding seems to have a promising future, as it can accelerate cement and pozzolanic reactions at early ages, optimising their microstructures, without compromising late strength and durability performances. In fact, these features could even be improved. Moreover, other uses are low temperature concreting, precasting, shotconcrete, etc. Here, we focus on reviewing recent reports on calcium silicate hydrate seeding using commercially available admixtures. Current knowledge on the consequences of nucleation seeding on hydration reactions and on early and late mechanical strengths is discussed. It is noted that other features, in addition to the classic alite hydration acceleration, are covered here including the enhanced ettringite precipitation and the very efficient porosity refinement, which take place in the seeded binders. Finally, because the seeded binders seem to be denser, durability properties could also be enhanced although this remains to be properly established.
Keywords: Química inorgánica; Cemento; Microestructuras; C-S-H nanoseeds; Accelerators; Admixtures; Ettringite; Microstructure